Efeito metafilático do disseleneto de difenila (PhSe)2 no desmame convencional e precoce de bezerras de corte - Parmeggiani, Eliana Burtet (2022)
Taking into account the challenge faced by beef heifers when they are weaned, the aim of the present study was to evaluate supplementation with diphenyl diselenide in conventional and early weaning. The methodology was similar for both studies, following the indicated sanitary and nutritional protocols, where the calves were distributed into three experimental groups: control group (CG): 2 mL of 0.9% NaCl solution; dimethylsulfoxide group (GDMSO): 2 mL of 99.2% DMSO; diphenyl diselenide (GDD) group: 3 μmol/kg of 98% (PhSe)2, diluted in 2 mL of DMSO. Collections and evaluations were performed at M1=baseline (-28) and M2 (-14) before weaning, M3 (0) day of weaning, M4 (14) and M5 (28) after weaning. The first study was carried out from April to June of 2021, with 31 calves with approximately six months of life, where the objective was to evaluate the metaphylactic effect of (PhSe)2, on body weight gain, biochemical parameters and oxidative status. The second was carried out from December 2021 to February 2022, with 30 calves with approximately 60 to 110 days of life, with the objective of evaluating the metaphylactic effect of diphenyl diselenide (PhSe)2 on weight gain body weight, total protein and oxidative status. Treatments were administered at times 1, 2 and 3, all subcutaneously. For blood collection, body weight assessment and treatment administration, the calves were led to a corral with a containment trunk suitable for the species. The calves were always kept in the same lot, under similar management and feeding conditions throughout the studies, with free access to water. Each experiment was carried out on a farm, depending on the weaning method carried out, the properties are bordering, with a similarity of soil and vegetation. Management in general was also quite similar between them, but we know that the chosen method influences individual responses, even if genetic, nutritional and environmental factors are similar. The results of the first study allowed us to conclude that (PhSe)2 increased the values of globulins and the antioxidant activity of reduced glutathione during the period of conventional weaning. In the second, although the practice was well executed following adequate sanitary and nutritional protocols, and with body weight gain by the calves at weaning, supplementation with diphenyl diselenide did not prevent the occurrence of oxidative stress in early weaning. In this way, weaning is an unconditioned experience that results in a high level of stress, but when carried out in an adjusted way, regardless of the chosen method, it helps to reduce the negative impacts.